The motion of light in water : sex and science fiction writing in the East Village, 1957-1965 - Delany, Samuel R. (Arbor House/William Morrow, 1988)
City's black ghetto Harlem at the start of World War II, Samuel R. Delany married white poet Marilyn Hacker right out of high school. The interracial couple moved into the city's new bohemian quarter, the Lower East Side, in summer 1961. Through the decade's opening years, new art, new sexual practices, new music, and new political awareness burgeoned among the crowded streets and cheap railroad apartments. Beautifully, vividly, insightfully, Delany calls up this era of exploration and adventure as he details his development as a black gay writer in an open marriage, with tertiary walk-ons by Bob Dylan, Stokely Carmichael, W. H. Auden, and James Baldwin, and a panoply of brilliantly drawn secondary characters. Winner of the 1989 Hugo Award for Non-fiction.